Systemic Lupus Erythematosus Presented with Bilateral Orbital Edema and Negative Serology - Manal Al-Khaldi; Manal Alsabbagh (Case Reports in Rheumatology)
Isolated bilateral periorbital edema with negative serology is an extremely rare presentation of cutaneous lupus erythematosus that may lead to eyelid scarring, infection, or even corneal involvement. The treatment usually comprises a combination of hydroxychloroquine and a tapering dose of systemic steroids. Patients require long-term follow-up as they may develop systemic lupus erythematosus with positive serology later in life. We report a case of a 32-year-old female who presented with chronic bilateral periorbital edema, and the histopathology confirmed cutaneous lupus erythematosus.